Clinical and subclinical characteristics of brain-dead donors for liver transplantation in Viet Duc University Hospital - Thanh Khiem Nguyen; Hong Son Trinh; Gia Anh Pham; Ham Hoi Nguyen; Trung Nghia Bui; Manh Thau Cao; Quang Nghia Nguyen; Viet Khai Ninh; Tuan Hiep Luong; Tien Quyet Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
Since 2010, 49 cases of liver transplants from brain-dead donors were performed at Viet Duc University Hospital. This study is a descriptive cross-section cohort study with a combined analysis of retrospective and prospective occurrences of a series of cases of liver procurement from brain-dead donors in Viet Duc University Hospital from March 2010 to March 2020. The results of this study showed several features: the average age of the brain-dead donors was 29.8±10.9 (18-69), donors were mostly male (7.17/1, 87.8%), and the main cause of brain death was head trauma. Clinically, 40.8 and 63.3% of the subjects were hypothermic and diagnosed with diabetes insipidus, however, the subjects were all well resuscitated before procurement. Therefore, haemodynamic indices and temperatures were maintained at stable levels and there was no statistically significant difference. In subclinical aspects, haemoglobin and platelet levels decreased significantly but remained within the target criteria during resuscitation while blood sodium levels increased significantly during resuscitation when compared with levels at the time of admission (p<0.001) thus corresponding to diabetes insipidus. In general, 44.90% of donors were within the ideal standard, and in the extended standard group, the highest rate was electrolyte disorders (32.65%). In conclusion, there are many variations in clinical and paraclinical body signs as well as homeostasis in the brain-dead donors. Of these signs, the most prominent were changes in haemodynamics, temperature, urine output, complete blood count, blood clotting, and blood sodium levels. These are all factors that are included in the criteria to consider the selection of a liver donor.